Student Movement Habituation of Good Practices to Realize Pancasila Student Profiles through Learning Based on Local Wisdom at SMA Masehi Berastagi - Christina Sitepu; Stepani Grace Zebua; Agusman Harefa; Grace Florida Manurung; Grace Pebrini Siallagan; Melati Riani Marbun; Novri Yenti Panjaitan; Ratna Sari Hutauruk (Jurnal Pengabdian Masyarakat Bestari, 2023)
Currently, many students do not understand the values ​​of Pancasila well and deeply. So, it is necessary to carry out activities at the Berastagi Christian High School with the theme of the student movement for good practice habits to realize the profile of Pancasila students through learning based on local wisdom. The activity was carried out through four stages, namely seven minutes with God, We Save The World (class cleanliness), Team Work (safety in class), and socialization of the Geogebra software. The results show an increase in students' understanding and appreciation of Pancasila values ​​and local wisdom. In addition, this activity also assists students in developing good attitudes and behavior through the habituation of good practices carried out in daily activities at school.